Corrigendum: Supported Discharge Teams for older people in hospital acute care: a randomized controlled trial - Parsons M; Parsons J; Rouse P; Pillai A; Mathieson S; Parsons R; Smith C; Kenealy T (Oxford University Press on behalf of the British Geriatrics Society, 2018)
The title of the above article originally contained a typing error, with the word 'hospital' being repeated in error. This has now been corrected in online and print versions. The authors apologize for this error.